The Italian public debate on same-sex civil unions and gay and lesbian parenting - Lasio, D. (2018)
After many years of heated debate, in 2016 the Italian parliament approved a law to regulate same-sex civil unions. Although this can be considered a significant step towards the equality of lesbian and gay couples, the law preserves legal differences between heterosexual marriage and homosexual union and does not guarantee the rights of lesbian and gay parents and their children. In this article, we analyze the public debate on same-sex couples and gay and lesbian parenting that occurred in Italy while the parliament was discussing the law. Findings highlight that the ‘natural order’ argument and the irreducible differences between heterosexual marriage and same-sex union are the bedrock of the current expression of heteronormativity in Italy.